Land Optimization for an Educational Greenhouse Through the Family Welfare Empowerment of Pengatigan Village, Rogojampi District, Banyuwangi - Utanaka, Ahmad; Budhi, Wahyu Satyaning; Indraloka, Aldy Bahaduri (Universitas Ahmad Dahlan, 2024)
Background : Pengatigan Village aims to repurpose vacant land behind the Village Office into a productive greenhouse, addressing land use challenges and empowering the community through the PKK. Contribution : The greenhouse will combine sustainable plant cultivation with education and empowerment, enhancing agricultural skills and fostering community development. Metode : The project involves coordination between village leaders and the PKK, integrating modern agricultural technologies like automated irrigation. Socialization programs will train PKK members in greenhouse operations. Results : The greenhouse transforms the land into an economic and educational resource, promoting sustainability, community empowerment, and serving as a model for other villages. Conclusion : The project creates a thriving community greenhouse, boosting local knowledge, economy, and sustainability efforts